(untitled) (Scientific journal of the Fergana State University, 2024)
In this article, based on historical and philosophical conditions, we have analyzed in detail the term institution of the family as a social system for the formation of family relations and the emergence of the institution of the family. We have traced the historical and philosophical conditions of the development of family and family relations, as well as the stages of the formation of value relations with the family in boys